Application of layer deposition manufacturing in the manufacture of centrifugal water pump blade master molds for aluminum casting process - Agus Suiiaryo (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
The mold master is a product that is used as a reference for making mold models. The mold master can also be said to be an original sample of a product to be developed. The goal to be achieved from this research is to apply the Layer Deposition Manufacturing (LDM) method for the development of small and medium industries in order to be able to make mold masters that are more complex in shape, especially for making centrifugal water pump mold master molds for the aluminum casting process. print master by utilizing CAD, then cutting the master per layer according to the product area boundaries, after being cut the data for each layer is saved to a file to be printed, the print results are pasted on the Win layer, then the pattern is cut using a pattern cutting machine, after the layer pattern is formed then the pouring of the material in the form of solid, liquid, powder is carried out in a controlled manner layer by layer until it is as high as the desired product. The application of the LDM method for the manufacture of mold masters in the aluminum casting industry is an alternative method which is easy and fast to manufacture. The advantages of LDM are that it can create hollow products, can experiment with physical objects with a high level of complexity, can optimize product design to meet customer demands. Meanwhile, the disadvantages of LDM are that the size produced is less precise, it requires a lot of material support, it cannot make thin products. The LDM method can be used to make mold masters, especially for centrifugal water pump blade mold masters, both simple and complex shapes.